Factors Which Made Holocaust Possible, Are Still With Us. Because We Are Still Modern - Bauman, Zygmunt (Communication Today, 2025)
Zygmunt Bauman (1925) is a Polish sociologist who left to England, where he has published his major works on modernity, Holocaust, globalization, consumerism, morality, rationality and social exclusion. In the Czech Republic and Slovakia, he has been well known since the sixties, when first translations of his books appeared. After 1989 other works were published, notably Modernity and the Holocaust, Globalization: The Human Consequences and Liquid Modernity. Zygmunt Bauman is one of the Europe’s most influential sociologists, British Guardian has labelled him “the most influential sociologist working in Europe.” Dennis Smith described Bauman as “the Prophet of Postmodernity” in a book of the same name from the series devoted to key contemporary thinkers. University of SS. Cyril and Methodius awarded him with a Degree of Doctor Honoris Causa upon Zygmunt Bauman on 5th November 2013.